A structural parameter to link molecular geometry to macroscopic orientation in discotic liquid crystals: study of metalloporphyrin tapes. Issue 10 (11th January 2021) - Kobayashi, Yoshiyuki; Muranaka, Atsuya; Kato, Kenichi; Saeki, Akinori; Tanaka, Takayuki; Uchiyama, Masanobu; Osuka, Atsuhiro; Aida, Takuzo; Sakurai, Tsuneaki
Abstract : A meso -alkyl triply-linked dimeric porphyrin tape forms a columnar liquid crystal mesophase, in which the macroscopic orientation of columns drastically changes depending on the choice of central metal ions. Abstract : Novel liquid crystalline (LC) molecules were prepared from a dimeric porphyrin tape. A series of metal complexes (1Zn, 1Pd, 1Cu, and 1Ni ) and the free-base form (12H ) of the porphyrin tape formed a columnar LC phase. Although only the central metal ions were different among these compounds, 1Ni, 12H, and 1Cu aligned homeotropically in a sandwiched glass cell, while 1Zn and 1Pd exhibited a random orientation at a macroscopic scale. The strength of the π–π interactions, tunable by the distortion of the porphyrin cores through metallation, is a key factor for the observed macroscopic orientation difference.